Evidence Based Practice Intradialytic Exercise untuk Pengelolaan Tekanan Darah pada Pasien Chronic Kidney Diseases (CKD) Stage V - Kusuma Prima Daniyati (LPPM STIKES NOTOKUSUMO YOGYAKARTA, 2013)
Background : Chronic Kidney Disease (CKD) is a progressive disorder of kidney function and can not be recovered back. Haemodialysis serves as replacement therapy of loss of kidney function. Patients typically undergo hemodialysis uraemic syndrome, a collection of symptoms that can lead to cardiovascular diseases, such as hypertension. Intradialytic exercise is an exercise that is done at the time of undergoing hemodialysis. Objective: This study aims to manage blood pressure in patients undergoing hemodialysis and hypertension by intradialytic exercise action. Method: The method used survey and used a sample of 30 people with the intake sample by purposive sample. Based on the measurement of blood pressure pre and post-exercise looks intradialytic blood pressure changes and blood pressure stability. Result: Based on the evaluation of the implementation of intradialytic exercise that has been carried out for 3 weeks (6 times exercise) occurs stability of blood pressure during exercise. The results of observations in patients who had stable blood pressure at pre and post-HD shows that they follow intradialytic exercise with the maximum movement in accordance with the instructions provided and regularly every 2 times a week. Whereas in patients who have unstable blood pressure at pre and post-HD can be affected by several factors such as frequency of exercise, stress conditions, and sleep disorders. Conclusion: Patients are expected to exercise regularly time of dialysis, so it can decrease blood pressure is near normal or blood pressure remained stable.